1988
DOI: 10.1111/j.2044-8295.1988.tb02285.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between phenomenal and objective aspects of concentration problems in depressed patients

Abstract: The paper explores a distinction between different kinds of lapse of concentration in depressed patients. The strategy is to begin with the phenomenological distinction between the mind (a) 'wandering' on to something else or (b) going 'blank'. Blanking, but not mind-wandering, is associated with longer planning times on the 'Tower of London' task. In contrast, mind-wandering but not blanking, is associated with poor memory for prose, at least under ordinary processing conditions. Different phenomenal forms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 8 publications
9
44
0
Order By: Relevance
“…In their seminal study, Golding and Singer (1983) reported that MW substantially explained variance in depressive attitudes, namely self-criticism, dependency, and inefficacy. In line with this, clinically and subclinically depressed samples show higher levels of MW (Smallwood, O'Connor, Sudbery, & Obonsawin, 2007;Watts, MacLeod, & Morris, 1988). Fourth, at the level of individual differences, depressive symptoms as well as rumination are worth mentioning.…”
Section: Introductionmentioning
confidence: 51%
“…In their seminal study, Golding and Singer (1983) reported that MW substantially explained variance in depressive attitudes, namely self-criticism, dependency, and inefficacy. In line with this, clinically and subclinically depressed samples show higher levels of MW (Smallwood, O'Connor, Sudbery, & Obonsawin, 2007;Watts, MacLeod, & Morris, 1988). Fourth, at the level of individual differences, depressive symptoms as well as rumination are worth mentioning.…”
Section: Introductionmentioning
confidence: 51%
“…Furthermore, although the two medicated Parkinson's disease groups were equally slow in initiating their solutions, they differed significantly in their accuracy of performance. Prolonged initial thinking times may also be attributed to mental activity that is not devoted to solving the problem at hand, resulting in 'blanking' or 'mind-wandering' (Watts et al, 1988). The former may be likened to the so-called 'psychic akinesia' occasionally reported in cases of Parkinson's disease (Hassler, 1953;Rogers, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 15 studies employing the Stroop Test, 36,78,79,88-90 the WCST, 21,67,69,72,88,91 or the Tower of London task [92][93][94] to evaluDegl'Innocenti and colleagues proposed that reduced rate of information processing was the primary problem for depressed subjects, Lemelin and coworkers 36 have asserted that, in addition, some depressed individuals have an impaired ability to inhibit distractors, and some have a resource-processing deficit.…”
Section: Executive Functionmentioning
confidence: 98%